OPTIMIZATION OF SAMA', BASHOR, AND AF'IDAH IN LEARNING THE SUBJECTS OF MORAL CREED IN MADRASAH IBTIDA'IYAH QODRATULLAH - Karmiza, Ebing; Muchtar, Aflatun; Sukardi, Ismail (Edukasi Islami: Jurnal Pendidikan Islam, 2024)
Islamic education is vital in determining and producing quality for the next generations; so far, Muslims have adopted more Western educational concepts. However, if Muslims examine more deeply, many Islamic concepts in the Qur'an that teach educational methods are more relevant to Muslims. This study will examine the "Optimization of same, Bashor, and af'idah in learning the subjects of moral creed in Madrasah Ibtida'iyah Qodratullah." This research uses qualitative methods, namely by prioritizing the results of observations and interviews. The results showed that Madrasah Ibtida'iyah Qodratullah teachers using the same concepts, Bashor and af'idah, with a combined approach or adjustment of auditorial, visual, and analytical methods in teaching moral creed subjects could provide a holistic and adaptive approach. By combining all three methods, teachers can create a rich and supportive learning environment, allowing students to understand religious values better. This holistic approach considers the diversity of student learning styles and provides space for each student to find the way of learning that works best for them. In other words, integrating these three methods provides flexibility and responsiveness to diverse learning needs.